Narcolepsy in early childhood: a case report and a Mini review - Liu, Guorui; Li, Guanxiong; Wang, Yihao; Yin, Ming; Pan, Wen; Zhao, Yu; Gao, Shigeng; Shi, Peiqi; Wen, Jing; Pan, Xiao; Wang, Yajing; Zhang, Yanfei (Frontiers in Pediatrics, 2025)
Narcolepsy is a sleep-wake disorder with an onset commonly seen in individuals aged 10–30 years. Due to various reasons, the diagnosis of narcolepsy often experiences a delay of at least ten years. Diagnosing narcolepsy in children is particularly challenging due to atypical symptoms, leading to frequent misdiagnosis or missed diagnoses. We report a case of narcolepsy in a four-year-old girl to provide insights into the early diagnosis and treatment of narcolepsy in children. As a chronic condition, narcolepsy can lead to decreased quality of life, including psychological issues such as depression and anxiety. Furthermore, there are few randomized controlled trials involving pediatric narcolepsy patients. To provide a comprehensive treatment approach for pediatric narcolepsy, we review the current progress in the treatment of narcolepsy in children.